Efektifitas Sistem Informasi Akuntansi Moka POS dalam Meningkatkan Kualitas Pelayanan - Fina Mulyana; Nurul Jannah; Yenni samri Juliati Nasution (Jurnal Proaksi, 2024)
The main issues in this research include the importance of accounting information systems in supporting business operational activities in improving service quality. Factors that influence the effectiveness of an accounting information system are the sophistication of the information system technology used, the system used must be good and successful in meeting user requests. The aim of this research is to implement an accounting information system in the form of the Moka Pos application properly and effectively so as to help overcome problems that often occur in the service process. The method used is qualitative in the form of a case study on sadistic coffee. The data used is primary data originating from interviews, observation and documentation. This research uses DeLone and McLean's theory. By interviewing the Sadis Coffee manager and 2 employees. The results of the research show that the Moka Pos (Point Of Sale) accounting information system implemented by Kopi Sadis is effective even though problems are found such as system errors and incorrect input. This can be overcome by periodically upgrading the system. The use of Moka Pos is considered to simplify the service process so that customers do not queue again.